Back Cover: Deeper Insight into the Six‐Step Domino Reaction of Aldehydes with Malononitrile and Evaluation of Antiviral and Antimalarial Activities of the Obtained Bicyclic Products (ChemistryOpen 3/2017). Issue 3 (30th May 2017) - Bock, Christina M.; Parameshwarappa, Gangajji; Bönisch, Simon; Bauer, Walter; Hutterer, Corina; Leidenberger, Maria; Friedrich, Oliver; Marschall, Manfred; Kappes, Barbara; Görling, Andreas; Tsogoeva, Svetlana B.
Abstract : The Back Cover picture highlights the easy generation of complex azabicyclic and carbobicyclic molecules from two simple compounds in a single operation through a highly efficient six‐step domino reaction. Within a multi‐step domino reaction, one transformation triggers the next, similar to a row of dominoes where one tile hits the next. The in vitro studies against the herpes virus and malaria reveal domino products as highly active compounds, outperforming the clinical reference drugs ganciclovir and chloroquine. More information can be found in the Full Paper by S. B. Tsogoeva and co‐workers onpage 364 in Issue 3, 2017 (10.1002/open.201700005 ).